PEMBELAJARAN CODING UNTUK MENINGKATKAN FOKUS BELAJAR ANAK USIA DINI STUDI KASUS DI TK ANAK CERIA KOTA BANDUNG - Deni Tirta Pawana Putra; Elistiana Wulan Sari; Sri Mustika; Waska Warta (STKIP Subang, 2025)
This mini research aims to describe how coding-based learning can improve the learning focus of early childhood students at TK Anak Ceria, Bandung. The study is motivated by the low attention span observed during conventional learning activities and the increasing need for digital literacy and computational thinking in the digital era. The research employed a qualitative descriptive approach, with data collected through observation, interviews, and documentation. Coding activities were introduced using unplugged methods, simple robotics, and visual applications such as ScratchJr. The PDCA (Plan–Do–Check–Act) management cycle was applied to ensure that the learning process remained systematic and continuously improved. The results indicate that coding activities enhance children’s attention, persistence, and ability to follow sequential instructions. Exploratory and visually engaging coding tasks helped children maintain their focus longer compared to traditional learning methods. This study provides preliminary evidence of coding’s potential as an innovative approach for early childhood education and serves as a foundation for developing technology-based learning management models in the future.